2021
DOI: 10.3389/fvets.2021.646839
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis Reveals the Role of Omp16 in Brucella-Infected RAW264.7 Cells

Abstract: Brucellosis is an endemic zoonotic infectious disease in the majority of developing countries, which causes huge economic losses. As immunogenic and protective antigens at the surface of Brucella spp., outer membrane proteins (Omps) are particularly attractive for developing vaccine and could have more relevant role in host–pathogen interactions. Omp16, a homolog to peptidoglycan-associated lipoproteins (Pals), is essential for Brucella survival in vitro. At present, the functions of Omp16 have been poorly stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…The functional enrichment analyses of the DE mRNAs and target genes of the DE lncRNAs showed that immune-related terms were enriched for the upregulated DE mRNAs and lncRNAs, and that metabolic-related terms were enriched for the downregulated DE mRNAs and DE lncRNAs. Similar results have been reported previously ( 66 , 67 ), further verifying our hypothesis that that the activity of immune-related genes was increased in the AN lambs and that the metabolic homeostasis was severely disrupted in the SE lambs during E. coli F17 infection. Notably, the PPAR signaling pathway was found enriched in KEGG enrichment analysis based on both DE lncRNAs and DE mRNAs.…”
Section: Discussionsupporting
confidence: 92%
“…The functional enrichment analyses of the DE mRNAs and target genes of the DE lncRNAs showed that immune-related terms were enriched for the upregulated DE mRNAs and lncRNAs, and that metabolic-related terms were enriched for the downregulated DE mRNAs and DE lncRNAs. Similar results have been reported previously ( 66 , 67 ), further verifying our hypothesis that that the activity of immune-related genes was increased in the AN lambs and that the metabolic homeostasis was severely disrupted in the SE lambs during E. coli F17 infection. Notably, the PPAR signaling pathway was found enriched in KEGG enrichment analysis based on both DE lncRNAs and DE mRNAs.…”
Section: Discussionsupporting
confidence: 92%
“…MiR-744 is known to be associated with the innate immunity pathway and acts as a tumor suppressor, thereby inhibiting cell proliferation and promoting cell apoptosis ( Pilson et al, 2020 ; Yuan et al, 2020 ). Meanwhile, the cytokine encoded genes, including IL-6 , IL-7 , IL-11 , IL-23A and IL-24 , were significantly changed in our RNA-seq data, which were partially consistent with previous studies ( Avila-Calderón et al, 2020 ; Zhou et al, 2021 ). IL-6 is a pleiotropic, pro-inflammatory cytokine produced by a variety of cell types, including lymphocytes, monocytes, and fibroblasts.…”
Section: Discussionsupporting
confidence: 92%
“…The interaction between Brucella and host immune system is critical for the development of persistent infection or infection clearance (8,18). To date, transcriptomic data derived from Brucella-infected mouse macrophages or mouse cell lines, domestic ruminants or Brucella-vaccinated animals (19)(20)(21)(22)(23)(24)(25). This study analyses, for the first time, the transcriptome profile, both in vitro, in Brucellainfected primary Mφ and PMNs, and ex-vivo, in PBMCs and PMNs derived from patients with acute brucellosis before and after treatment.…”
Section: Discussionmentioning
confidence: 99%